2006
DOI: 10.1300/j158v06n02_01
|View full text |Cite
|
Sign up to set email alerts
|

Treating Insanity Acquittees with Personality Disorders: Implementing Dialectical Behavior Therapy in a Forensic Hospital

Abstract: Treating personality disordered patients in forensic settings is a daunting task for mental health practitioners. Such patients are frequently violent and disruptive to traditional treatment programs. Given this diagnostic group, forensic programs must implement specialized treatment for patients with borderline and antisocial personality disorders that demonstrate effectiveness in reducing violence and assist in preparing patients for potential release back to the community. In addition, treatment programs sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…Given the associations between BPD and violence (Newhill, Eack, & Mulvey, 2009; Raine, 1993; Vaughn, Newhill, Litschge, & Howard, 2006) the disorder requires therapeutic management. Therapy programs like Dialectical Behavior Therapy (DBT; Linehan, 1993) have shown to be relatively effective teaching females to regulate emotions and developing interpersonal skills offers some promise for reducing recidivism and violence (Nee & Farman, 2005; Newhill & Mulvey, 2002; Vitacco & VanRybroek, 2006). However, DBT has also proven effective in treating substance abuse (Bornovalova & Daughters, 2007; Dimeff, Rizvi, Brown, & Linehan, 2000; McMain, Sayrs, Dimeff, & Linehan, 2007), an issue that can lead to revocation of conditional release.…”
Section: Discussionmentioning
confidence: 99%
“…Given the associations between BPD and violence (Newhill, Eack, & Mulvey, 2009; Raine, 1993; Vaughn, Newhill, Litschge, & Howard, 2006) the disorder requires therapeutic management. Therapy programs like Dialectical Behavior Therapy (DBT; Linehan, 1993) have shown to be relatively effective teaching females to regulate emotions and developing interpersonal skills offers some promise for reducing recidivism and violence (Nee & Farman, 2005; Newhill & Mulvey, 2002; Vitacco & VanRybroek, 2006). However, DBT has also proven effective in treating substance abuse (Bornovalova & Daughters, 2007; Dimeff, Rizvi, Brown, & Linehan, 2000; McMain, Sayrs, Dimeff, & Linehan, 2007), an issue that can lead to revocation of conditional release.…”
Section: Discussionmentioning
confidence: 99%
“…There have been multiple studies showing that specific treatment protocols can be effective at reducing inpatient violence (Evershed et al, 2003). As an illustrative example, dialectical behavior therapy (DBT) is frequently used within inpatient settings (Vitacco & Van Rybroek, 2006). In addition, DBT offers potential to reduce recidivism risk once an individual is discharged from a secure setting (Tomlinson, 2018).…”
Section: Developing Specific Interventions For Violence Preventionmentioning
confidence: 99%
“…The treatment of personality disorders and psychopathy have also garnered attention. The use of DBT for personality-disordered acquittees has been identified as a means of helping to reduce core symptoms that increase the risk for aggression, manage challenging behaviors in an institutional setting, and prepare the acquittee for community transition (Vitacco & Van Rybroek, 2006). One case study identified psychodynamic art psychotherapy as a potentially effective treatment for those with antisocial personality disorder (Hackett, 2019), while others have maintained that psychopathy itself has not been shown to be treatable in standard NGRI inpatient programs, (Felthous, 2011).…”
Section: Treatment Of Subpopulations Of Insanity Acquitteesmentioning
confidence: 99%